晚唐五代苦吟诗人心态与社会现实 的相关性 ：剖析“苦中作乐”之悖论 = The correlation between society and the psychological state of the "bitter recitation" poets from late Tang to five dynasties : the paradox of seeking pleasure in bitterness - 陈韦廷 Tan, Vivian Wan Teng (2015)
苦吟是中晚唐时期继安史之乱后极为重要的诗坛现象。特别是到了晚唐五代期间，苦吟诗的创作逐渐成熟化。苦吟诗的流行无疑与当代的社会状态有着密不可分的关系。安史之乱所带来的影响使得唐王朝日益衰落，以至最终的灭亡。笔者希望从社会角度探究诗人的内心情感是如何反应在诗作中。苦吟诗人从表面上看似过得很苦，但笔者坚信每个人都有适应周边环境的能力，即便社会现实使诗人们的人生困苦，但社会中的潜在因素总有办法让他们在逆境中找到生存的力量与希望。本文将重点放在晚唐五代的社会以及其环境因素对于苦吟诗人心态的影响。在这时期的诗人往往为了想要将自己的情感表达得更加细腻，而不断地在语句上进行雕琢，而 这另诗人从中获得无比的满足感，找到自己的生活价值。另外，还能给予些诗人一种精神上的寄托。再来基于在当时佛教禅学的影响力也让诗人们学习到做人要懂得释怀、放下。 笔者透过结合晚唐社会风貌以及诗人们本身的经历与心理因素来做出详细的分析，发现情绪往往反映在作品中。之后便从中揭示出诗人在苦吟背后的深层蕴涵；既在苦吟背后并非纯苦，反而潜在的是苦与乐情绪相并存、从而产生复杂的情感交叉。 Bitter Recitation（苦吟） was first popularized in Mid Tang and subsequently thrived during the era between Late Tang to the Five Dynasties as the style of writing matured. This tumultuous period could be largely attributed to the An-Shi Rebellion which was the main turning point leading to the eventual demise of the Tang Dynasty. The theory of Social Psychology serves to explain that human minds are constantly being shaped and influenced by day to day interactions with the society together with its prevailing social circumstances and the poets that engage in "bitter recitation" are of no exception. In this scenario, harsh social conditions influenced and pushed the poets towards the extreme, resulting in them experiencing mixed and complicated feelings. The focus of this paper seeks to examine the inner feelings of these poets and to delve in deeper to unveil the possible feelings of pleasure and happiness behind the poems that portrayed deep feelings of pain, bitterness and suffering. Common composition styles of the poets includes undergoing rigorous processes to achieve the perfect choice of word, sentence structure; providing them with an avenue to rant and release all the negative feelings felt within; as well as the incorporation of Zen Buddhism teachings. Through analyzing the writing styles of the poems coupled with the consideration of the social environment as an important contributing factor, it engages us to think critically beyond the surface of words that seemed to be completely filled with sadness and to realise that even deeper feelings and meaning lies behind the veil where rigorous choosing of words should be understood as the pursuit of artistic work and that strong feelings of satisfaction would emerge upon achieving the perfect line; perceiving the value of composition as equivalent to one's life and serves as an intimate private space for the poets to unleash all their feelings in exchange for comfort of the mind; while the teachings of Zen Buddhism actually provides peace, thereby ensuring a calm state of psychological well-being. All of these explains how the process of poets reciting bitterly could in actual fact possibly be a form of enjoyment for them at the same time. However, in the understanding of this paper, it is important to take note that no absolute feelings of either complete sadness or complete happiness felt by the poets should be assumed.